Analysis of Annual and Seasonal Temperature Trends at Zuwara Station for the Period 1951–2020 - د. نعيمة موسى الشامخ (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to analyze the trends in the temperature changes in Zuwara region over the period (1951–2020) by examining annual, seasonal, and monthly temperature variations and identifying their trends. The results revealed an increase in the mean maximum temperature in the Zuwara region. The statistical analysis employed included linear regression model and the (t-test) to determine the significance of the changes. The study results indicate that there is a statistically significant increasing trend in the annual average temperature for the period (1951–2020). The same pattern were found in the seasonal averages for the period (1986 –2020), where the mean maximum temperature increased by Cº2.015 with a correlation coefficient (R²) of 0.93 and a high statistical significance (p < 0.001). The results also showed that the highest rate of increase occurred in the summer season with a rate of Cº0.73, while the winter season showed a significant rise in the maximum temperature by Cº0.91 at a significance level of 0.023.